Implementation of Informed Consent on Hormonal Injection Contraceptive Family Plan Method Acceptor: A Phenomenology Study - Eufrasia Prinata Padeng; Putriatri Krimasusini Senudin; Dionesia Octaviani Laput; Eugenius Rada Masri (Alta Dharma Publisher, 2021)
Every medical treatment conducted by health professionals have to be based on the consent from patients. This consent obtained through informed consent. Informed consent is a communication process between health professionals and patient on approving the medical treatment. The objective of this study was to identify the implementation of informed consent on the acceptor of hormonal injection contraceptive family plan method. This study was a qualitative study using phenomenology approach, which the data analysis initialized by reducing interview result, then data were verified using data triangulation and the research conclussion developed. The participant of this study were 3 midwives and 1 primary midwife. The study identified three (3) themes on the implementation of informed consent namely human resources, the implementation of informed consent and the related policy to implement informed consent on prefering the hormonal injection contraceptive. The acceptor adherence on signing the informed consent are considered low thus the health education and approach of informed consent from health professionals are important to increase public awareness paetu=icularly the family plan contraceptive acceptor.